2018
DOI: 10.1002/jcla.22414
|View full text |Cite
|
Sign up to set email alerts
|

Rare LPL gene missense mutation in an infant with hypertriglyceridemia

Abstract: We have here identified a rare pathogenic mutation in the LPL gene in a Chinese infant with severe hypertriglyceridemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…After transfecting Leu279Arg cDNA in COS-1 cells, Chan et al did not detect LPL activity in the cell culture medium and lysate. It was speculated that Leu279Arg could influence the stability of LPL dimers and cause the lack of mutant protein secretion [ 31 ]. The heparin-binding site of LPL is located at residues 279–282 and 292–304 in the N-terminal region; Leu279Arg is located in the N-terminal heparin-binding region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After transfecting Leu279Arg cDNA in COS-1 cells, Chan et al did not detect LPL activity in the cell culture medium and lysate. It was speculated that Leu279Arg could influence the stability of LPL dimers and cause the lack of mutant protein secretion [ 31 ]. The heparin-binding site of LPL is located at residues 279–282 and 292–304 in the N-terminal region; Leu279Arg is located in the N-terminal heparin-binding region.…”
Section: Discussionmentioning
confidence: 99%
“…If the process is disturbed, LPL cannot be outside of the cell and exert its lipolytic activity. Qin et al reported a Chinese family with high plasma triglycerides linked to Leu279Arg heterozygous mutation [ 31 ]. In this family, both sister and the father were carriers of the Leu279Arg heterozygous mutation.…”
Section: Discussionmentioning
confidence: 99%
“…LPL is produced in adipocytes and (cardio)myocytes and is transported by the endothelium-derived protein GPIHBP1 to the capillary surface, where it acts to hydrolyze plasma TG ( 10 , 11 ). In line with its rate-limiting role in TG uptake, mutations in LPL are associated with severe hypertriglyceridemia in humans and mice ( 12 , 13 ). The activity of LPL in different tissues is meticulously regulated to match the mobilization of TG-derived fatty acids to the local tissue demand ( 7 ).…”
mentioning
confidence: 99%